Pengaruh Peran Inovasi Berbasis AI, Kapabilitas Digital, dan Strategi Fokus dalam Meningkatkan Pertumbuhan Ekonomi Berkelanjutan pada UMKM Join Us Caffe di Bandung, Indonesia - Tini Kartini; Yesi Amelia; Anggi Mahmuddin; Megha Sakova (Indo Publishing, 2026)
This study aims to analyze the influence of Artificial Intelligence (AI)-Based Innovation, Digital Capabilities, and Focus Strategies on Sustainable Economic Growth at Join Us Caffe, an SME in Bandung, Indonesia, both partially and simultaneously. This study employs a quantitative approach using an associative-causal method. The study population consisted of 37 respondents, all of whom were included in the sample using total sampling. Data were collected through a questionnaire using a Likert scale and analyzed using path analysis with the aid of IBM SPSS software. The results show that, when analyzed partially, Digital Capabilities have a positive and significant effect on Sustainable Economic Growth, while AI-Based Innovation and Focus Strategy do not have a significant effect. Simultaneously, AI-Based Innovation, Digital Capabilities, and Focused Strategy have a positive and significant effect on Sustainable Economic Growth. The test results show an Adjusted R-Square value of 0.510, meaning that the three independent variables account for 51.0% of the variation in Sustainable Economic Growth, while the remaining 49.0% is influenced by other factors outside the research model. These findings indicate that Digital Capabilities play the most significant role in supporting sustainable economic growth at Join Us Caffe, an SME, while the implementation of AI-Based Innovation and Focused Strategy requires support from other factors to contribute more effectively to business sustainability